CONCERNING CONSUMER PROTECTION: - Asra Febriani Asra; Erlisa Sukma (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2021)
This article discusses the differences in guarantee law in Islamic sharia and the Indonesian legal system. Both systems agreed that if the product is not in a good condition, it is a must for the seller to provide a guarantee as to his responsibility to the customer. It is called ‘khiyar disgrace’ in the perspective of Islamic law and ‘garansi’ in Indonesian law. Using library sources this article showed that khiyar disgrace has the relations and comparisons with the guarantee law on consumer protection. The similarity between both ‘khiyar aib’ and ‘garansi’ is that if the sold item is broken, flawed, or damaged, the buyer could make a complaint and receive a replacement for the broken item. The difference between the two is that in ‘khiyar disgrace’, the flaw of the transacted item should be found before the transaction whereas, in ‘garansi’, the guarantee is given to the customer when the flaw of the sold item is found after the items are traded.